I love you, Mister Bear - Kantorovitz, Sylvie ([New York, NY] : HarperCollins Publishers, 2003)
Young Sosha buys a shaggy old teddy bear at a yard sale and brings him home for some special care and love.
"A Junior Library Guild Selection"-- Jkt. flap.
Keywords: Teddy bears -- Fiction; Teddy bears -- Juvenile fiction